If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -4(y + 7) = 7 + 3y Reorder the terms: 9 + -4(7 + y) = 7 + 3y 9 + (7 * -4 + y * -4) = 7 + 3y 9 + (-28 + -4y) = 7 + 3y Combine like terms: 9 + -28 = -19 -19 + -4y = 7 + 3y Solving -19 + -4y = 7 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. -19 + -4y + -3y = 7 + 3y + -3y Combine like terms: -4y + -3y = -7y -19 + -7y = 7 + 3y + -3y Combine like terms: 3y + -3y = 0 -19 + -7y = 7 + 0 -19 + -7y = 7 Add '19' to each side of the equation. -19 + 19 + -7y = 7 + 19 Combine like terms: -19 + 19 = 0 0 + -7y = 7 + 19 -7y = 7 + 19 Combine like terms: 7 + 19 = 26 -7y = 26 Divide each side by '-7'. y = -3.714285714 Simplifying y = -3.714285714
| x^4+9x^2+400=0 | | 3b-2=19 | | 2x-3+5x=4+4x+1 | | 2x+y-2z=2 | | s^2+9s+81=0 | | 7*6= | | 89-7x=29x+21 | | X^3=81x | | x-4y+2z=-11 | | 26=7x+x+2 | | 30-5a=10 | | -.5(y+5)=-1 | | c/8+10=15 | | 3x+2y-4z=3 | | c/8=15 | | 12x^2+12x-24=0 | | 12-10x=62-24x | | -7(x+1)=2x-34 | | 24a-22=-4(1-6n) | | -x+3=-3x+11 | | 4x^2-48+44=0 | | x^2+36x=144 | | 6x-3=2x+5 | | 9x(3x)2x= | | 8x+9+2(10+x)=2x+29 | | 0.4x-0.6x-5=1 | | x=35 | | x^2+36x-144=0 | | -.33m-7=5 | | 26x-2-13x=10x+5+3x | | 29x-7-11x=15x+9+3x | | x^2+3x-9=3x |